Globalisasi dan Pembelajaran Sosial-Emosional Berbasis Pendidikan Islam : Globalization and Social-Emotional Learning Based on Islamic Education - Nufus, Dewi Hayati; Abdul Mu’ti; Alpha Amirrachman (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2023)
The reseacrh aims to develop the concept of social-emotional learning based on Islamic education in order to enhance students' social and emotional intelligence in Islamic educational institutions in light of difficulties with globalization. The research uses a qualitative approach with library research. Data collection through literature searches was obtained from primary data sources, namely the Qur'an and books of interpretation, and secondary data, namely from various literature books, journals, and other research results relevant to the theme. Data analysis techniques use descriptive and interpretive content analysis which is carried out by reading and reviewing/analyzing the data sources collected. The research results found that the concept of social-emotional learning is based on the main character principles of the characters described in Q.S. al-Aḥzāb/33: 35 as Ten Excellent Characteristics which can be developed into a Social-Emotional Learning program curriculum for students in Islamic educational institutions. The concept of social emotional learning based on Islamic education with specifications on the character concept explained in Q.S. al-Aḥzāb/33: 35 is a catalyst for the development of character education which can be developed in further research to be implemented.